Rainfall-Runoff Response of A Suburban Area - Kasmin, Hartini; Wai Tan, Lai; Abdul Rahim, Muhammad Afiq; Md Ali, Zarina; Isa, Nur Fitriah (International Journal of Integrated Engineering, 2023)
Batu Pahat experiences flash floods whenever intense rainfall coincides with high tide. Among the factors which cause flash floods are due to Batu Pahat river catchment's flat and low-lying geographical features as well as high-intensity rainfall. The goals of the study are to analyse the frequency of rainfall events for SMK Munshi Sulaiman station and to investigate runoff due to severe rainfall events within the study area. The observed daily rainfall depth record between 2010 and 2021 was obtained from the Department of Irrigation and Drainage (DID) Malaysia. The frequency of rainfall events within the 11-year period is examined using empirical rainfall intensity formulation. Rainfall-runoff of the five most heavy rainfall events in 2021 within the study area are simulated using HEC-HMS. It has been found that most daily rainfall events have a frequency of a 1-year return period. Only three events were found to have a return period of up to 2-year ARI, with a maximum rainfall depth of 110.67 mm. Five heaviest rainfall events in 2021 were obtained from DID's real-time online platform for rainfall-runoff simulations. One of the events, which occurred in June 2021 has a frequency larger than a 100-year return period while other events have return periods ranging from 1-year to 5-year. Simulations produced by HEC-HMS for these events in January, April, May, June, and September 2021 have resulted in peak flow of 6.7 m3/s, 26.8 m3/s, 24.7 m3/s, 39.9 m3/s, and 39.9 m3/s, respectively. Based on frequency analysis, rainfall-runoff simulations, and field observations, it can be concluded that flash floods are highly possible due to high-intensity rainfall as well as lowland topographical features of the study area. Therefore, flood mitigation measures need to be carried out to improve the drainage system for the suburban area.